2015
DOI: 10.2337/dc15-1360
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in and Prognostic Value of Biomarkers of Hyperglycemia

Abstract: OBJECTIVEWe compared levels and associations of traditional (fasting glucose, HbA1c) and nontraditional (fructosamine, glycated albumin, and 1,5-anhydroglucitol [1,5-AG]) biomarkers of hyperglycemia with incident cardiovascular disease (CVD), incident end-stage renal disease (ESRD), and prevalent retinopathy in black and white adults.RESEARCH DESIGN AND METHODSWe included 10,373 participants without (8,096 white, 2,277 black) and 727 with diagnosed diabetes (425 white, 302 black) from the Atherosclerosis Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…In other studies in ARIC, we also observed that associations of nontraditional biomarkers of hyperglycemia (fructosamine and glycated albumin) with clinical outcomes were also similar in blacks and whites (39). Ultimately, the literature suggests that HbA 1c is a similarly valid diagnostic and prognostic tool in persons of different races/ethnicities and supports recommendations for using the same HbA 1c diagnostic cut points across racial/ethnic groups (10,70).…”
Section: Prognostic Value Of Hba1c In Different Racial/ethnic Groupssupporting
confidence: 76%
See 1 more Smart Citation
“…In other studies in ARIC, we also observed that associations of nontraditional biomarkers of hyperglycemia (fructosamine and glycated albumin) with clinical outcomes were also similar in blacks and whites (39). Ultimately, the literature suggests that HbA 1c is a similarly valid diagnostic and prognostic tool in persons of different races/ethnicities and supports recommendations for using the same HbA 1c diagnostic cut points across racial/ethnic groups (10,70).…”
Section: Prognostic Value Of Hba1c In Different Racial/ethnic Groupssupporting
confidence: 76%
“…Importantly, the higher levels of HbA 1c are also seen for other biomarkers of chronic hyperglycemia, specifically fructosamine and glycated albumin (3942). Because fructosamine and glycated albumin are unaffected by the hematologic factors that might affect HbA 1c , racial differences in erythrocyte turnover or hemoglobin glycation cannot explain racial differences in these hemoglobin-independent serum biomarkers of hyperglycemia.…”
Section: What Might Explain Racial Differences In Hba1c?mentioning
confidence: 99%
“…l,5-AG is inversely associated with blood glucose concentrations as a result of competitive inhibition by glucose in the proximal tubule [4] and is thought to be useful for intermediate-term monitoring of glycaemic variability in people with diabetes [5]. In epidemiological studies, low concentrations have been associated with greater diabetes risk [6,7] and, in the setting of diabetes with retinopathy, chronic kidney disease [7][8][9] and cardiovascular disease [10,11]. In people without diabetes, 1,5-AG may reflect carbohydrate digestion [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, young people of African descent have increased risk of short‐term complications (ketoacidosis and severe hypoglycemia) when adjusted for socioeconomic status, and higher HbA1c even when adjusted for mean glucose levels . HbA1c was higher even when fasting glucose is <7 mmol/L in black individuals both with and without diabetes compared with white, but the prognostic value of HbA1c for predicting cardiovascular disease, nephropathy and retinopathy were similar …”
Section: Care For the Preschool Child With Type 1 Diabetes In Limitedmentioning
confidence: 99%
“…171 HbA1c was higher even when fasting glucose is <7 mmol/L in black individuals both with and without diabetes compared with white, but the prognostic value of HbA1c for predicting cardiovascular disease, nephropathy and retinopathy were similar. 172 The financial issues need to be addressed upfront by the treating team. The challenge of finding ways to support the families lies chiefly with the care providers.…”
Section: Care For the Preschool Child With Type 1 Diabetes In Limitmentioning
confidence: 99%